Model-based optimisation of a batch reactor with a coupled bi-enzymatic process for mannitol production. (2nd February 2020) - Maria, Gheorghe
Highlights: Fructose (F) is reduced to mannitol (M) using MDH (mannitol dehydrogenase) and NADH. Cofactor NADH is in-situ continuously recovered by the expense of formate degradation. Formate enzymatic degradation takes place simultaneously in the presence of free FDH. Model-based simulation allows optimization of coupled reactions in a batch reactor. For an imposed fructose reduction conversion, enzyme consumption is minimized. Abstract: Multi-enzymatic reactions are effective alternatives to complex chemical syntheses, using milder reaction conditions, and generating less waste. One essential engineering problem concerns derivation of an optimal operation policy of the chosen reactor. For coupled enzymatic systems, model-based calculations turn into difficult optimization problem to be solved for every particular system. The paper exemplifies model-based identification of the optimal operating policy of a bi-enzymatic batch reactor (BR), that minimizes enzyme consumption for an imposed productivity. Exemplification refers to the enzymatic reduction of d -fructose to mannitol by using suspended MDH and NADH cofactor, with in-situ continuous regeneration of NADH by the expense of formate enzymatic degradation. As novelty items are worth mentioning: (i) highlighting the close connection between the coupling reactions, enzyme concentrations, and quasi-stationary NADH/NAD ratio over the batch; (ii) how a lumped but adequately dynamic model can successfully support in silico engineering evaluations by aiming to optimize the BR operation. Graphical abstract: Image, graphical abstract